Регулирование информационного взаимодействия государственных органов с гражданами и организациями Украины - Палениус, А. (Культура народов Причерноморья, 2005)
The system of a uniform information support of authorities and local management units is the integral part of information society and "E-government" of Ukraine. Its main objective is to provide efficiency for collection of information, creation of information resources, access to the information of authorities and the citizens, rise of efficiency of accepted solutions, support of information interactions of authorities; rendering real services from the state authorities to its citizens. Creation of such a system calls for enforcement issues inside the state bodies of the defined functions, development projects to define the rules in using interaction with citizens, implementations of the methods of process concepts and analysis of economic and social information.